SOCIAL FACTORS AFFECTING CHILD EDUCATION PSYCHOLOGICAL FACTORS (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
This article analyzes the psychological factors affecting child upbringing in the family. The role of family education in the formation of a child as a person is highlighted.